Biodegradable and water-soluble polycarboxylates derived from starch - Isananto Winursito (Majalah Kulit, Karet, dan Plastik, 2012)
abstractThis research present electrical and thermal properties of the Nano composite high density poly Utilizationof natural resources, like polysaccharide, as a raw material for the preparation of biodegradable andfunctional polymer was studied. Partially dicarboxylated polysaccharides were prepared using starch fromcorn, sago and tapioca, and comparison was made of their biodegradability, hydrolytic degradability andcalcium ion sequestration capacity. The biodegradability of dicarboxylated starch sodium salt (DC-starch)depended on the dicarboxylation degree. DC-starch containing more than 75-85 mol% of unreactedglucopyranose groups in the polymer chain showed excellent biodegradation. DC-starch with highdicarboxylation degree was resistant to biodegradation but showed good calcium ion sequestration.Among DC-starches from corn, sago and tapioca starches, hydrolytic degradability and calcium ionsequestration performance were essentially the same.Keywords: biodegradation, dicarboxylated starch, polycarboxylate, water-soluble polymer.